Proteomic analysis of middle and late stages of bread wheat (Triticum aestivum L.) grain development - Zhang, Ning; Chen, Feng; Huo, wang; Cui, Dangqun (Frontiers in Plant Science, 2015)
Proteomic approaches were applied in four grain developmental stages of the Chinese bread wheat Yunong 201 and its ethyl methanesulfonate (EMS) mutant line Yunong 3114. 2-DE and tandem MALDI-TOF/TOF-MS analyzed proteome characteristics during middle and late grain development of the Chinese bread wheat Yunong 201 and its EMS mutant line Yunong 3114 with larger grain sizes. We identified 130 differentially accumulated protein spots representing 88 unique proteins, and four main expression patterns displayed a dynamic description of middle and late grain formation. Those identified protein species participated in eight biochemical processes: stress/defense, carbohydrate metabolism, protein synthesis/assembly/degradation, storage proteins, energy production and transportation, photosynthesis, transcription/translation, signal transduction. Comparative proteomic characterization demonstrated 12 protein spots that co-accumulated in the two wheat cultivars with different expression patterns, and 6 cultivar-specific protein spots including serpin, small heat shock protein, beta-amylase, alpha-amylase inhibitor, dimeric alpha-amylase inhibitor precursor, and cold regulated protein. These cultivar-specific protein spots possibly resulted in differential yield-related traits of the two wheat cultivars. Our results provide valuable information for dissection of molecular and genetics basis of yield-related traits in bread wheat and the proteomic characterization in this study could also provide insights in the biology of late grain development.